Child Sexual Assault as a Risk Factor for Mental Disorders Among Women - A Community Survey - Kilpatrick, Dean G.; Veronen, Lois J.; Villeponteaux, Lorenz A.; Lipovsky, Julie A. (Journal of interpersonal violence, 1992)
A community sample of 391 adult women was screened for a history of sexual assault during childhood and assessed for lifetime and current mental disorders using a structured victimization history interview and the Diagnostic Interview Schedule. One third of the women had been victims of rape, molestation, or sexual assault not involving physical contact prior to the age of 18 years. Child rape victims were more likely than nonvictims to have ever met DSM-III diagnostic criteria for a major depressive episode, agoraphobia, obsessive-compulsive disorder, social phobia, and sexual disorders. Molestation victims were overrepresented on major depressive episode, obsessive-compulsive disorder, and sexual disorders. Noncontact child sexual assault was not a significant risk factor for any disorder. Child rape and molestation victims were more likely than victims of noncontact assault to have had crime-related posttraumatic stress disorder. Mental disorder lifetime prevalence risk ratios for child rape and molestation victims versus nonvictims ranged from 1.5 for major depressive episode to 6.7 for obsessive-compulsive disorder